Changes in vaginal cytokines concentrations during artificial insemination and natural service in beef heifers - Kyle J. McLean; Taylor B. Ault-Seay; Phillip R. Myer (BMC Research Notes)
Abstract Objective Heifer development is crucial for the optimization of reproductive efficiency in beef production. Heifer development is largely influenced by nutrition. Nutritional status of these heifers can influence immunological responses that are crucial for reproduction. Commercial Angus heifers (n = 9) were utilized, in a pilot study, to elucidate the effects of sampling time (days 0, 7, 14, 21, 28, and 35), pregnancy status, and type of mating on individual cytokine concentrations and cytokine profiles in the vagina following breeding. Results Cytokine profiles were analyzed using MetaboAnalyst 5.0 and one-way ANOVAs were performed in R Studio to identify differences in individual cytokines based on sampling time, pregnancy status, and type of mating. Cytokine profiles were different (P = 0.05) 7 days after either mating type. Cytokines, IL-1β, IL-17a, MCP-1, and TNFα were different based on the mating type and pregnancy status. Multiple cytokines, IL-1α, IL-1β, IL-6, IL-8, IL-10, IL-17a, VEGFa, and MIP1α, were different between days regardless of pregnancy status. In conclusion, vaginal cytokines differ based on pregnancy status, type of mating, and time which may be indicative of vital pathways that need to be activated for pregnancy.